Value relevance do valor distribuído da demonstração do valora adicionado: análise no mercado brasileiro à luz da teoria dos Stakeholders e Shareholders - Couto, Marcia Helena de Andrade (2020)
The objective of this study was to analyse the behaviour of the relevance of the informational content of the distribution of the value of the AVD, according to the interest groups classified in the light of the Stakeholders and Shareholders Theory. The methodology applied was the qualitative and quantitative approach, from 2009 to 2018, in 169 Brazilian companies. The data were organized in a panel, totaling 1,690 observations, and the Ohlson (1995) model of value relevance adjusted according to the survey was used. The Vad variables were classified into VadShare (Shareholders), VadStake (Stakeholders), StakSoc (Social), StakGov (Government) and StakTer (Third Parties) and the research hypotheses based on economic theory. The results showed that Vad provides a more adequate model and has a negative influence on stock prices, confirming the economic theory. The maximization of wealth to shareholders is confirmed in the results of regressions in all interest groups in the distribution of wealth - it was found that the VadShare model is the most appropriate when compared with VadStake, StakSoc, StakGov and StakTer. It was found that the period analyzed, of economic and political crisis, influenced the behavior of the value of the distribution of wealth, the price of shares and the average negative performance. In general, it can be inferred that other factors can impact the stock price. It is important to note that both the discussion of the theory of Shareholders and Stakeholders and the analysis of the empirical evidence may be the awakening of interest in analysis and discussions in academia and greater use and utility of VAD in companies and the market.